Video Games in Rehabilitation Programs for People with Parkinson’s Disease: A Systematic Review - Isabel Quirosa-Galán; Sara García-Bravo; Anthia Cristina Fabara-Rodríguez; Mª Pilar Rodríguez-Pérez; Elisabet Huertas-Hoyas; Jorge Pérez-Corrales; Gemma Fernández-Gómez; Madeleine Donovan; Cristina García-Bravo (Applied Sciences)
Background: Parkinson’s disease is a neurodegenerative disorder affecting the central and peripheral nervous systems. Its treatment combines pharmacological and rehabilitative approaches, aimed at improving motor symptoms and preventing cognitive decline. Virtual reality emerges as a complementary rehabilitative option, showing efficacy in enhancing motor and cognitive aspects. This study systematically reviews the effectiveness of virtual reality in the rehabilitation of individuals with Parkinson’s disease. Methods: A systematic review was carried out. The Jadad scale was used to assess the methodological quality of the included studies, and the Oxford Center for Evidence-Based Medicine criteria were applied to determine the level of evidence and recommendation. The review followed PRISMA guidelines, with a literature search conducted in databases such as Cochrane and PubMed. Results: The studies indicate improvements in gait, balance, and overall motor function in Parkinson’s patients using virtual reality, though limitations such as small sample sizes and the lack of control groups in some studies are noted. Conclusions: Virtual reality proves to be an effective tool in Parkinson’s rehabilitation, enhancing balance and motor function. However, more studies with adequate methodological quality and larger sample sizes are needed to validate these findings.